Accumulation of glutamate by Salmonella typhimurium in response to osmotic stress. - Botsford, J L (1994)
Salmonella typhimurium accumulates glutamate in response to osmotic stress. Cells in aerobic exponential growth have an intracellular pool of approximately 125 nmol of glutamate mg of protein-1. When cells were grown in minimal medium with 500 mM NaCl, KCl, or sucrose, 290 to 430 nmol of glutamate was found to accumulate. Values were lower when cells were harvested in stationary phase. Cells were grown in conventional medium, harvested, washed, resuspended in the control medium or in medium with osmolytes, and aerated for 1 h. With aeration, glutamate was found to accumulate at levels comparable to those observed in exponential cultures. Antibiotics inhibiting protein synthesis did not affect glutamate accumulation when cells were aerated. Strains with mutations in glutamate synthase (glt) or in glutamate dehydrogenase (gdh) accumulated nearly normal levels of glutamate under these conditions. A double (gdh glt) mutant accumulated much less glutamate (63.9 nmol mg of protein-1), but a 1.9-fold excess accumulated when cells were aerated with osmotic stress. Methionine sulfone, an inhibitor of glutamate synthase, did not prevent accumulation of glutamate in cells aerated with osmotic stress. Glutamate dehydrogenase is thought to have minimum activity when ammonium is limiting. Resuspending cells with limiting ammonium reduced glutamate production but did not eliminate accumulation of excess glutamate when cells were osmotically stressed. Amino oxyacetic acid, an inhibitor of transamination reactions, did not prevent accumulation of excess glutamate.(ABSTRACT TRUNCATED AT 250 WORDS)